Implications of government policies and programs on climate change adaption, mitigation, and resilience in agriculture in South Asia - Tyagi, Narendra K.; Aggarwal, Pramod K.; Joshi, P.K.; Pandey D (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Contains the following headlines: Background. National level policies and programs. Impact indicators and approach. Impact of government policies and programs. Way forward. Conclusions.